Endoscopic ultrasonography‐guided hepaticogastrostomy using a novel laser‐cut type partially covered self‐expandable metal stent (with video). Issue 7 (28th July 2021) - Ogura, Takeshi; Kitano, Masayuki; Okuda, Atsushi; Itonaga, Masahiro; Ueno, Saori; Yamashita, Yasunobu; Nishioka, Nobu; Ashida, Reiko; Miyano, Akira; Higuchi, Kazuhide
Abstract : Endoscopic ultrasonography (EUS)‐guided hepaticogastrostomy (HGS) is of clinical benefit in patients with failed endoscopic retrograde cholangiopancreatography (ERCP). However, some endoscopists are concerned about the potential risk of adverse events. Bile peritonitis due to bile leakage through the fistula is one of the possible adverse events following EUS‐HGS. Recently, a novel laser‐cut type partially covered self‐expandable metal stent (PCSEMS), which is a dedicated stent for EUS‐HGS, has become available. This stent has an uncovered part, despite it being a laser‐cut type stent, along with a flared end. In addition, it uses a 7‐Fr stent delivery. Therefore, tract dilation might not be needed to deploy the stent, which might reduce the incidence of stent migration. In this study, the safety of EUS‐HGS using this novel laser‐cut type PCSEMS was evaluated by assessing technical success, which was defined as successful stent deployment, and clinical success, which was defined as reduction in serum total bilirubin levels by 50% and resolution of symptoms related to biliary tract obstruction within 2 weeks. Five patients with unresectable malignant biliary obstruction underwent EUS‐HGS using the novel stent. Stent deployment was successfully performed without tract dilation in four patients, although tract dilation using a balloon catheter was needed in one patient. Clinical success was obtained in all patients, and adverse events including abdominal pain and bile peritonitis were not observed in any of the patients. EUS‐HGS without tract dilation can be safely performed using a novel laser‐cut type PCSEMS. A prospective comparative study evaluating this stent versus conventional stents is needed to corroborate our results.